The Effectiveness Of The Application Of Nursing Early Warning Score System (NEWSS) In Reducing The Frequency Of Emergency Cardiac Arrest: A Case Study Of Pelamonia Hospital, Makassar - Nusdin Nunu Nusdin (International Journal of Nursing and Health Services (IJNHS), 2020)
One of the efforts made by nurses to identify deterioration or emergency incidents in patients is through the use of Nursing Early Warning Score System (NEWSS). This study therefore aims to determine the effectiveness of this system in reducing the frequency of cardiac arrest in patients. A quasi-experiment with a post-test only control group design was adopted and a sample of 80 respondents was obtained. Furthermore, the research instrument consists of 7 physiological parameters in the NEWSS assessment, under standard operating procedures. The results from the Mann Whitney test with a P value of 0.000, (P <0.05) indicate that the System is effective in reducing the frequency of emergency cardiac arrests. Keywords: NEWSS, Cardiac Arrest Emergency